Extensive Expansion of A1 Family Aspartic Proteinases in Fungi Revealed by Evolutionary Analyses of 107 Complete Eukaryotic Proteomes - Revuelta, María Victoria (2014)
The A1 family of eukaryotic aspartic proteinases (APs) forms one of the 16 AP families. Although one of the best characterized families, the recent increase in genome sequence data has revealed many fungal AP homologs with novel sequence characteristics. This study was performed to explore the fungal AP sequence space and to obtain an in-depth understanding of fungal AP evolution. Using a comprehensive phylogeny of approximately 700 AP sequences from the complete proteomes of 87 fungi and 20 nonfungal eukaryotes, 11 major clades of APs were defined of which clade I largely corresponds to the A1A subfamily of pepsin-archetype APs. Clade II largely corresponds to the A1B subfamily of nepenthesin-archetype APs. Remarkably, the nine other clades contain only fungal APs, thus indicating that fungal APs have undergone a large sequence diversification. The topology of the tree indicates that fungal APs have been subject to both “birth and death” evolution and “functional redundancy and diversification.” This is substantiated by coclustering of certain functional sequence characteristics. A meta-analysis toward the identification of Cluster Determining Positions (CDPs) was performed in order to investigate the structural and biochemical basis for diversification. Seven CDPs contribute to the secondary structure of the enzyme. Three other CDPs are found in the vicinity of the substrate binding cleft. Tree topology, the large sequence variation among fungal APs, and the apparent functional diversification suggest that an amendment to update the current A1 AP classification based on a comprehensive phylogenetic clustering might contribute to refinement of the classification in the MEROPS peptidase database.